Prospects for shipping in 2013 & beyond (LNG Sector) - Heng, Yang Ling. (2013)
The project provides an evaluation and analysis on the prospects for the liquefied natural gas (LNG) shipping sector in the next five years. With rapid changes occurring at short intervals, looking at long term prospects may not be appropriate as it may not be easy to provide a good prediction in such a dynamic environment. Moreover, in such situations, investors usually refrain from long term investment due to the higher risk exposure.